Assessment of noise-induced hearing loss (NIHL) of weaving factory workers in West Bengal, India - a pilot study - Patel, Jigisha; Ghosh, Tirthankar (International Journal of Occupational Safety and Health, 2023)
Introduction: Excessive noise exposure is one of the majorly considered occupational stress for industrial workers. The operation of steel weaving machinery producing a high level of noise such as weaving machines, crimping machines, and hydraulic press machines for a prolonged period increases the risk of developing noise-induced hearing loss (NIHL). The main aim of the study was to assess the auditory health of the workers exposed to a high level of noise in a steel weaving factory and the prevalence of NIHL among workers. Methods: 26 subjects in the age group of 25-55 years from a steel weaving industry of Chinsurah town, Hooghly district of West Bengal were randomly selected with 5 years of exposure for the study. The control group was selected from the same age group, socioeconomic status and geographical location and having no history of such exposure. The physiological parameters of the workers, noise levels in the workplace and auditory functions and the risk of NIHL were assessed by standardized protocol and statistically analyzed. Results: The study indicated that steel weaving factory workers had significantly reduced hearing functionality at 4000Hz and 6000Hz in the left ear respectively. It also revealed that the workers were exposed to high noise exposure of 131dB near weaving machine, 113dB at crimping machine, and 84dB at hydraulic press machine respectively. Conclusion: A high level of noise exposure leads to deterioration in the hearing capabilities of the steel weaving industrial workers. Implementation of ergonomic interventions in the workplace and the use of personal protective equipment (PPE) may decrease the prevalence of NIHL and can help to prevent hearing loss in workers.